Evaluating Sharia Banking Financial Performance Before and After Initial Public Offering Using Risk Profile, Good Corporate Governance, Earning and Capital - Dzikra Azzahra; Izra Berakon (FEBI UIN Sunan Kalijaga, 2021)
Initial Public Offering is one of the steps that companies can take in order to obtain capital through the shares sold. Through the Islamic capital market, Islamic banking can increase its competitiveness and capital through the industry. The purpose of this study was to assess whether there were changes in the financial performance of Islamic banking before and after the IPO with the Risk Profile, Good Corporate Governance, Earning and Capital Methods (RGEC) approach which was further developed into financial ratios of NPF, FDR, ROA, ROE, and CAR. And to find out whether the decision of Islamic banking to conduct an IPO has been effectively carried out. This study uses the Wilcoxon test to see if the performance of Islamic banks that conducted an IPO in 2018 (Bank BTPN Syariah Tbk. and Bank BRI Syariah Tbk.) changed after conducting an initial public offering. The result is that the average FDR, CAR, and ROE ratios have a significant difference in the financial performance of Islamic banking before and after the IPO and there is no significant difference between the ROA and NP ratios.